2011
DOI: 10.1111/j.1369-7625.2011.00675.x
|View full text |Cite
|
Sign up to set email alerts
|

Responses to procedural information about colorectal cancer screening using faecal occult blood testing: the role of consideration of future consequences

Abstract: Background Colorectal cancer (CRC) screening participation is low despite its effectiveness in reducing CRC mortality. Identifying benefits and barriers requires consideration of specific characteristics of screening modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 52 publications
3
30
0
Order By: Relevance
“…Cole et al (2003) claimed that this was because taking fewer samples makes the test more convenient and lessens the aversion to handle faecal samples. These findings support von Wagner et al (2011) andWeller et al (2009), and provide a possible explanation as to why the FIT was not as favourable in Levi et al (2011); i.e. because participants were required to take the same amount of samples for the FIT as the G-FOBt.…”
Section: Discussionsupporting
confidence: 68%
“…Cole et al (2003) claimed that this was because taking fewer samples makes the test more convenient and lessens the aversion to handle faecal samples. These findings support von Wagner et al (2011) andWeller et al (2009), and provide a possible explanation as to why the FIT was not as favourable in Levi et al (2011); i.e. because participants were required to take the same amount of samples for the FIT as the G-FOBt.…”
Section: Discussionsupporting
confidence: 68%
“…The responsibility for completing the screening test by the individual and any perceived difficulty may lead to lower levels of participation. Von Wagner and colleagues found that the intention to participate in CRC screening decreased when participants were given detailed information about how to collect fecal samples for a guaiacbased FOBT (32). The FIT, which does not require dietary restrictions and only one stool sample, has been found to result in significantly higher participation rates than the guaiac-based FOBT (30,36).…”
Section: Discussionmentioning
confidence: 99%
“…Whether or not a reduction in the number of dietary restrictions will lead to improved screening participation has yet to be determined. Research has also found that individuals are more reluctant to participate in CRC screening if they perceive the test as impractical, awkward, or embarrassing (32)(33)(34). The guaiacbased FOBT requires individuals to apply a small sample from three separate bowel movements onto a test card with the aid of a cardboard spatula (35).…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is a leading cause of cancer death in North America (American Cancer Society 2012;Canadian Cancer Society 2011;von Wagner et al 2012); upwards of 1 million cases are newly diagnosed each year (Center et al 2009; International Agency for Research on Cancer 2008). The risk of CRC includes a substantial heritable component (Dunlop et al 2012;Hawken et al 2010), largely consisting of numerous low penetrance variants (Hawken et al 2010;Khoury et al 2004).…”
Section: Cancer Screeningmentioning
confidence: 99%